2006
DOI: 10.1007/s00497-006-0034-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of the pollen-expressed polymorphic F-box genes linked to the S-locus in apple (Malus × domestica)

Abstract: Using degenerate primers designed based on the conserved regions of the reported SLF/SFB genes, more than a dozen of different cDNA clones were isolated from pollen of three different apple S-genotypes by reverse transcription (RT)-PCR. The 5¢-and 3¢-rapid amplification of cDNA end in combination with RT-PCR allowed isolation of two fulllength cDNAs, whose corresponding genes (RJ28-2 and Mg15, later renamed SLF 1 and SLF 2 ) were specifically expressed in pollen in an S-haplotype-specific manner. PCR analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 42 publications
2
37
0
1
Order By: Relevance
“…Similarly, a pollen-S candidate has been identified by sequencing a 317-kb region of the S 9 -locus in apple and PCR with degenerate primers derived from the conserved regions of Prunus pollen-S (Cheng et al, 2006). Although Cheng et al (2006) isolated a single Slocus-linked F-box gene from different S-alleles, Sassa et al (2007) isolated multiple F-box genes (SFBBs) in a genome region that encodes a certain S-haplotype. SFBBs are specifically expressed in pollen, and variable regions of SFBBs are under positive selection.…”
Section: Identification Of Pollen-s Candidates In Malus and Pyrusmentioning
confidence: 99%
“…Similarly, a pollen-S candidate has been identified by sequencing a 317-kb region of the S 9 -locus in apple and PCR with degenerate primers derived from the conserved regions of Prunus pollen-S (Cheng et al, 2006). Although Cheng et al (2006) isolated a single Slocus-linked F-box gene from different S-alleles, Sassa et al (2007) isolated multiple F-box genes (SFBBs) in a genome region that encodes a certain S-haplotype. SFBBs are specifically expressed in pollen, and variable regions of SFBBs are under positive selection.…”
Section: Identification Of Pollen-s Candidates In Malus and Pyrusmentioning
confidence: 99%
“…However, genes for the pollen S-determinant in Malus species, belonging to the Maloideae subfamily, have not been functionally characterized (Cheng et al 2006;Kakui et al 2007Kakui et al , 2011Okada et al 2008Okada et al , 2011Sassa et al 2007Sassa et al , 2010.…”
mentioning
confidence: 99%
“…The gametophytic self-incompatibility (GSI) system in apple is controlled by a multiallelic single locus, called Slocus [13,14]. The genes responsible for apple GSI, (S-RNase as the pistil factor and SFB/SLF as the pollen factor) have been cloned [15,16]. Both, S-RNase and SFB/SLF are located at the S-locus, and their combined alleles are called S-haplotype for they are tightly linked.…”
Section: Cross-compatibility Among Wild Apples Crab Apples (Pollenizmentioning
confidence: 99%
“…In the case of commercial cultivars, the central flower opened first followed by the laterals [8]. I observed that the opening of the central flower of "Fuji" was between half a day and one day earlier than that of the laterals at Nagoya, Japan, in 2013 (the temperature during the flowering period at day time was [13][14][15][16][17][18][19][20][21][22][23] ∘ C). Also in the case of "Maypole, " the central flower opened first at all 5 to 7 flower clusters investigated.…”
Section: Introductionmentioning
confidence: 99%